PENEMPATAN APARATUR SIPIL NEGARA (ASN) PADA JABATAN STRUKTURAL DI DINAS SOSIAL KAB. KEP. TALAUD - WALONI, YOSUA; RORONG, ARIE; LALOMA, ALDEN (Sam Ratulangi University, 2019)
The placement of a Civil State Apparatus on structural position is a process which is very decisive in getting competent employees in their fields, because the exact placement in the proper positions will be able to help a the Agency in achieving the expected objectives. Placement is one of the important aspects in the human resources planning process, as it relates to efficiency and fairness. This research aims to find out how the placement of the Civil State Apparatus on structural position in the service of Social Government Talaud Islands. This research uses qualitative research methods. Based on the results of the study found that education, knowledge, skills, experience and age factor of a Civil State Apparatus became a benchmark in placing employees on structural position in the service of Social Government Talaud Islands. The Basic Social Service should be more effective and efficient in putting employees on structural position.Keywords: Placement, Structural Position, Civil State Apparatus.